(untitled) (Arsi Journal of Science and Innovation, 2025)
Abstract This investigation examined the mediation effect of strategic alignment, strategic foresight, intellectual capital and firm performance of manufacturing SMEs in Sidama regional state, Ethiopia. The study's target population comprised of 4,000 members of staff from 30 small and medium-sized manufacturing companies. The researchers employed a method called systematic random sampling to choose 363 respondents to take part in the study. To collect data, the researchers used structured questionnaire. Using AMOS software, the researchers applied methods such exploratory factor analysis (EFA), Kaiser-Meyer-Olkin (KMO) measure, and structural equation modeling (SEM). The results showed that Firm performance and strategic alignment, as well as strategic foresight and Firm performance, are significantly correlated. Intellectual capital was also found to be an important mediator, improving the efficiency of both strategic alignment and strategic foresight in reaching competitive results. The findings emphasize how crucial it is to incorporate intellectual capital development into strategic management procedures and how SMEs must cultivate an aligned and forward-thinking culture. For managers and policymakers looking to improve SMEs' strategic competencies in a changing business environment, this research adds to understanding of how these constructs interact to affect Firm performance.